Operation of the Kazakhstan Republic Constitution: Legal, Value and Functional Content - Abdrasulov, Ermek B.; Onlanbekova, Galiia M.; Abdrasulova, Aizhan E. (The journal of contemporary issues in business and government, 2021)
The subject of the research is the category “operating of the Constitution” and its constituent elements: use, observance, implementation and Constitution’s norms application. In this article, the analysis of the functions and meaning of operating of the Constitution is determined from the standpoint of the methodology of the theory of law, which provides for the need to study state- legal phenomena, focusing on legal practice. In this regard, the conclusions of the study are based on the legal positions and legal provisions of the constitutional control body and the judiciary. The article emphasizes that the value content of the Constitution, the purposefulness, stability, constancy and duration of its operation are determined by the functions of the Constitution, which reveal such an important quality of it as a direct and indirect impact on social relations. Based on the analysis of legal literature and practice, it is concluded that the establishment of legal links between the Constitution and the sectoral law is the task of the legislator and the body of constitutional control, rather than the subject of the application of law, for which an ordinary law may be a priority in relation to constitutional norms. At the same time, we also show the grounds for the direct application of the norms of the Constitution, except for the objective limits and restrictions reflected in the work.